EFFECT OF THE ORTHOSIPHON STAMINEUS, BENTH ON AMINOPYRINE METABOLISM IN RAT HEPATOCYTES - CHIN JIN HAN1; ABAS HJ. HUSSIN (Universiti Sains Malaysia, 2007)
One of the commonly used herbal medicines in Malaysia is Orthosiphon stamineus, Benth (family: Lamiaceae) or locally known as Misai Kucing. This experiment was undertaken to evaluate possible interaction of methanol extract of O. stamineus with aminopyrine, a model drug, in different age groups (young, adult and old) of Sprague-Dawley (SD) female rat hepatocytes. Hepatocytes were prepared by collagenase perfusion technique. Determination of aminopyrine N-demethylase activity was done by measuring formaldehyde formed. From these findings, only normal young female rat hepatocytes in the presence of 0.001 mg/ml of methanol extract of O. stamineus showed significant increase in aminopyrine N-demethylase activity. However, aminopyrine N-demethylase activity was not affected in hepatocytes of normal adult and old female SD rats. In conclusion, exposure of methanol extract of O. stamineus could affect phase I aminopyrine metabolism in normal young female SD rat hepatocytes but this effect was age-dependent.